Freedom from Medicare: Maternal Activists, Organized Business, and Popular Mobilization against the Welfare State During the Saskatchewan Doctors’ Strike, 1962 - Langford, Will (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2025)
In July 1962, Saskatchewan doctors went on strike in a refusal to work under the Medicare Care Act, which introduced universal health insurance in the province. The much-studied conflict between organized medicine and the Co-operative Commonwealth Federation government has been understood as a decisive moment in the history of public healthcare in Canada. Less studied, but equally important, the doctors were supported by a larger protest movement that set out to oppose the expansion of the welfare state. This article reveals that an alliance between maternal activists who started the Keep Our Doctors committee, businessmen who aimed to foster popular anti-statism through the Canadian Chamber of Commerce’s Operation Freedom and the Free Citizens Association, and doctors was an unplanned coalition, but not something that emerged entirely by chance. The agitation was a form of conservative populism resolved, in exaggerated fashion, against compulsion, increased taxation, and alleged communism. It was also part of a distinctive transnational moment of right-wing radicalization. Principles of democracy and freedom united opponents of Medicare in Saskatchewan and linked them with American radical right peers in ways specific to the early 1960s.